2009
DOI: 10.1211/jpp/61.02.0001
|View full text |Cite
|
Sign up to set email alerts
|

Review: doxorubicin delivery systems based on chitosan for cancer therapy

Abstract: Objectives This review sheds insight into an increasingly popular polymer that has been widely explored as a potential drug delivery system. The abundant, biodegradable and biocompatible polysaccharide chitosan, with many other favourable properties, has been favoured as a drug delivery system for the purposes of encapsulating and delivery of doxorubicin with reduced side-effects. Key findings Doxorubicin is frequently used as a frontline chemotherapeutic agent against a variety of cancers. It has largely been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 95 publications
1
34
0
1
Order By: Relevance
“…Previous works by Jain and colleagues 46 have demonstrated that the increases in tumour vascular permeability form the basis for nanoparticle extravasation and drug delivery. Recently, works by Dass and colleagues 48 have shown that chitosan-based delivery systems are efficient for cancer therapy. Along with these studies, current advances in nanotechnology have produced synthetic nanoparticles to encapsulate and release a pre-programmed diversity of therapeutic measures against cancers 1,2,4,49-51 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous works by Jain and colleagues 46 have demonstrated that the increases in tumour vascular permeability form the basis for nanoparticle extravasation and drug delivery. Recently, works by Dass and colleagues 48 have shown that chitosan-based delivery systems are efficient for cancer therapy. Along with these studies, current advances in nanotechnology have produced synthetic nanoparticles to encapsulate and release a pre-programmed diversity of therapeutic measures against cancers 1,2,4,49-51 .…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The second class includes doxorubicin and daunorubicin; they inhibit class II topoisomerases progression, preventing the DNA double helix from being resealed and therefore stopping cell division. 19,20 Two cell lines derive from lung carcinoma (A549 and A427); two other cell lines come from prostate carcinoma (PC-3 and DU145). The last three (T98G, U373 and Hs683) are glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Chitosan is a carbohydrate polymer with the desirable properties of biodegradability and biocompatibility that have made it a candidate polymer for preparation of drug delivery carriers. [21][22][23][24][25][26][27][28][29] Several methods have been developed for the preparation of doxorubicin delivery systems based on chitosan, 30 which include dextran sulfate-chitosan hydrogel nanoparticles, glycol-chitosan nanoaggregates, oleoyl-chitosan nanoparticles, chitosan-poly(acrylic acid) hollow nanospheres, and stearic acid-grafted chitosan oligosaccharide micelles.…”
Section: Introductionmentioning
confidence: 99%